Orthogonal array design for optimization of an artificial medium for in vitro rearing of Trichogramma dendrolimi. Issue 1 (27th May 2014) - Lü, Xin; Han, Shichou; De Clercq, Patrick; Dai, Jianqing; Li, Liying
Abstract Successful complete development of Trichogramma species on artificial media is also related to the presence and proportions of ingredients other than host insect‐derived components. In this study, an orthogonal array with six factors at three levels was performed and parameters of parasitism, larval development, pupation, and adult emergence were monitored to reveal the most important components of an artificial medium and to improve the medium for in vitro mass rearing of Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae). Results indicated that biological parameters of T. dendrolimi were affected differently by six ingredients of the artificial medium: pupal hemolymph of Antheraea pernyi (Guérin‐Méneville) (Lepidoptera: Saturniidae), egg yolk, 10% malted milk solution, Neisenheimer's salt solution, trehalose, and sterile water. Statistical analysis indicated that trehalose and Neisenheimer's salt solution, 10% malted milk solution, and pupal hemolymph of A. pernyi were the main ingredients of the artificial medium based on rates of parasitism and pupation, the number of larvae developing in each artificial egg, adult emergence rate, and the number of normal adults produced. A follow‐up bioassay with a selection of optimized formulas confirmed the validity of the optimization as predicted by the orthogonal array analysis, indicating the usefulness of this method for selecting artificial diets for entomophagous insects. Adult emergence rate of the parasitoid and total number of normal adults produced per egg card (each containing 20 artificial eggs) averaged 88.8% and 956 females on the best performing optimized artificial medium, consisting of 3 ml pupal hemolymph of A. pernyi, 2.5 ml egg yolk, 1 ml 10% malted milk solution, 1 ml Neisenheimer's salt solution, 0.1 g trehalose, and 1.5 ml sterile water. The latter medium was superior to any formerly developed medium and may thus have potential for the in vitro mass rearing of T. dendrolimi.